Reasons for freehold homeownership of the younger generations to live in vertical housing in the Greater Jakarta Metropolitan Area, Indonesia - Pratami Fadillah; Joko Adianto (International Journal of Built Environment and Scientific Research, 2024)
This research aims to discover the reasons for the reasons for homeownership for the younger generations with vertical housing preferences in the Greater Jakarta Metropolitan Area (GJMA). Indonesia's population, which is dominated by the millennial and Z generations, has led to an increase in housing needs. The housing preferences of the younger generation based on their characteristics and lifestyle in megapolitan cities are suitable for vertical housing. Quantitative methods were used on 807 respondents in Indonesia with a five-point Likert scale and several open-ended questions about hobbies, reasons for owning a house, and perceived difficulties in owning a house. The results of descriptive statistical analysis and cross-tab analysis of the tabulated primary data-based coding show that the characteristics and lifestyles of the younger generation, as well as housing values, are more dominant. Identification of the factors associated with the characteristics that fall into the category of housing values was done through multiple linear regression analysis. The results of this study inform the level of importance of homeownership among young people with vertical housing preferences in urban and suburban areas within marital status classifications. This study contributes to the improvement of future housing policies for Millennials and Gen Z.